Beyond the “Politics of Toil”: Collective Mobilization and Individual Activism in Toronto’s Portuguese Community, 1950s–1990s - Fernandes, Gilberto (Urban History Review / Revue d'histoire urbaine, 2010)
The following article examines the changing political attitudes of Portuguese immigrants in Canada from the arrival of the first cohort in the 1950s to the emergence of the second and third generations in Canadian mainstream society in the 1990s. It explores historical factors that have influenced the political profile of Portuguese Canadians, including its predominantly working-class makeup; its lack of formal education and democratic culture resulting from Portugal’s authoritarian legacy; and its internal factionalism along regional, ideological, generational, and class lines. Fernandes offers a historical critique of sociological models— “socio-economic status” and “socialization”—commonly used for measuring and explaining immigrant political participation, and stresses the importance of diachronic studies in dispelling essentialist assumptions regarding immigrant communities. The author argues that generalist notions of “political participation” and “political constituency” miss important distinctions between representative and direct forms of political action, collective mobilization and individual activism, as well as state level and grassroots politics. He claims that each of these political processes operates according to its own distinct internal dynamics, at times responsive, at other times alienated from one another, which must be analyzed using appropriate scales of observation (macro and micro).